Tobacco Use Among Racial and Ethnic Population Subgroups of Adolescents in the United States - Ralph S. Caraballo, PhD, MPH; Sue Lin Yee, MA, MPH; Joseph C. Gfroerer; Terry F. Pechacek, PhD; Rosemarie Henson, MSSW, MPH (Preventing Chronic Disease, 2006)
Introduction Limited data on cigarette smoking among population subgroups hinder the development and implementation of intervention strategies for those subgroups. Because of small sample sizes or inadequate study formats, cigarette smoking among youths has been studied mostly among broad racial or ethnic categories (e.g., Asian, Hispanic) instead of subgroups (e.g., Vietnamese, Cuban). The objective of this study was to evaluate cigarette smoking among U.S. youths by racial and ethnic subgroups. Methods The study used a nationally representative sample of youths aged 12 to 17 years who participated in the National Survey on Drug Use and Health in 1999, 2000, or 2001. Outcomes measured include prevalence of cigarette smoking, mean age of smoking initiation, and susceptibility to start smoking. Results The prevalence of smoking among youths aged 12 to 17 years varied among racial and ethnic subgroups, ranging from 27.9% for American Indians and Alaska Natives to 5.2% for Japanese. Among youths aged 12 to 17 years, the age of smoking initiation ranged from 11.5 years (American Indians and Alaska Natives) to 13.2 years (Japanese); the overall mean age of initiation was 12.3 years. White and African American youths were the only groups that showed a significant sex difference in age of initiation among all 14 subgroups; white and African American boys initiated smoking a few months earlier than white and African American girls. One of every four never-smokers aged 12 to 17 years was classified as susceptible to becoming a smoker. Conclusion The prevalence of cigarette smoking among youths varies widely by racial and ethnic subgroup. There is a need for sustained, culturally appropriate interventions to prevent and control cigarette smoking among youths, particularly within racial and ethnic subgroups with a high prevalence of cigarette smoking.